Pediatric types I and VI choledochal cysts complicated with acute pancreatitis and spontaneous perforation: A case report and literature review. Issue 42 (October 2017) - Tsai, Ching-Chung; Huang, Po-Kai; Liu, Hsien-Kuan; Su, Yu-Tsun; Yang, Ming-Chun; Yeh, Ming-Lun
Abstract: Rationale: Choledochal cysts are a congenital disorder of the common bile duct that can cause progressive biliary obstruction and biliary cirrhosis. They were classified by Todani into five types. Of these, type VI choledochal cysts are rarely reported in the literature. Patient concerns: A 22-month-old girl presented with intermittent epigastralgia for approximately 10 days and fever for three days. Fasting and total parenteral nutrition were administered after admission. However, sudden onset of severe epigastric pain occurred. An abdominal sonogram showed turbid ascites and peritonitis was impressed. Diagnoses: An emergent exploratory laparotomy was performed, and perforation of the posterior wall of types I and VI choledochal cysts was observed. Interventions: Intraoperative cholangiography revealed concomitant types I and VI choledochal cysts with stricture of the distal common bile duct. Definite surgery for resection of the choledochal cysts and gallbladder was performed with Roux-en-Y choledochojejunostomy. Outcomes: The patient had no evidence of ascending cholangitis at three years after the operation. Lessons: Type VI choledochal cysts are rarely reported in the literature. To our knowledge, this is the first reported pediatric case of concomitant types I and VI choledochal cysts complicated with acute pancreatitis and spontaneous perforation.